Energy Beyond Food: Foraging Theory Informs Time Spent in Thermals by a Large Soaring Bird - Shepard, Emily L. C. (Public Library of Science, 2011)
Current understanding of how animals search for and exploit food resources is based on microeconomic models. Although widely used to examine feeding, such constructs should inform other energy-harvesting situations where theoretical assumptions are met. In fact, some animals extract non-food forms of energy from the environment, such as birds that soar in updraughts. This study examined whether the gains in potential energy (altitude) followed efficiency-maximising predictions in the world's heaviest soaring bird, the Andean condor (Vultur gryphus). Animal-attached technology was used to record condor flight paths in three-dimensions. Tracks showed that time spent in patchy thermals was broadly consistent with a strategy to maximise the rate of potential energy gain. However, the rate of climb just prior to leaving a thermal increased with thermal strength and exit altitude. This suggests higher rates of energetic gain may not be advantageous where the resulting gain in altitude would lead to a reduction in the ability to search the ground for food. Consequently, soaring behaviour appeared to be modulated by the need to reconcile differing potential energy and food energy distributions. We suggest that foraging constructs may provide insight into the exploitation of non-food energy forms, and that non-food energy distributions may be more important in informing patterns of movement and residency over a range of scales than previously considered.